Method for passivating defects of perovskite thin film and application
By introducing passivation molecules with carboxyl, imino, and amino functional groups, the method addresses defects in perovskite films, achieving high efficiency and stability in perovskite solar cells.
Patent Information
- Application Number
- CN202411314517.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-20
AI Technical Summary
Perovskite solar cells face defects that lead to non-radiative recombination of carriers, carrier transfer barriers, and susceptibility to environmental factors like water and oxygen, reducing efficiency and stability.
Introduce the passivation molecules with carboxyl, imino, and amino groups to perovskite compounds to form new compounds that passivate the defects of the perovskite films in multiple dimensions, achieving comprehensive passivation of the defects of the defects of the defects of the defects of the defects of the defects of the defects of the defects of the defects of the defects of the defects of the perovskite film, thereby improving the photoelectric conversion efficiency and stability.
The method achieves comprehensive passivation of perovskite solar cells, enhancing photoelectric conversion efficiency to 25.40% and maintaining 93% of initial efficiency after 1200 hours in ambient air, with improved moisture resistance and thermal stability.
Smart Images

Figure CN119173115A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of perovskite solar cells, and in particular relates to a method for passivating defects in a perovskite film and an application thereof. Background Art
[0002] With the increasing depletion of traditional fossil energy and the growing demand for energy, finding a new renewable energy source has become a new challenge facing human society. Solar energy is an important renewable energy source and is increasingly valued by researchers. At present, the most widely used way to utilize solar energy is to use the photovoltaic effect of semiconductor materials to prepare solar cell devices, thereby converting solar energy into electrical energy. Therefore, the development of new high-efficiency and low-cost solar cells has become a necessary technical basis for realizing the application of solar photovoltaic power generation.
[0003] As a representative of the third generation of thin-film batteries, perovskite solar cells have the advantages of high conversion efficiency, low cost, low pollution, and simple preparation process. Thanks to the excellent photoelectric properties of perovskite materials, such as high absorption coefficient, adjustable band gap, high carrier mobility, long carrier lifetime and diffusion length, the highest certified efficiency of perovskite solar cells has reached 26.21%, showing broad application prospects. The general chemical formula of perovskite compounds is ABX3, where A is usually a rare earth or alkaline earth metal element with a larger radius, such as Ca, Sr, and Ba; B is a transition metal element with a smaller radius, such as Ti, Mn, Fe, Co, etc., which is usually the main component that determines many properties of perovskite structure type materials due to its variability in valence; X is O or halogen, such as I, Cl. Common perovskites include LaMnO3, BiFeO3, CsPbI3, etc.
[0004] As the light-absorbing layer of perovskite solar cells, the perovskite layer is crucial to the performance of the cell. Since the perovskite film has a fast crystallization rate and many defects, the defects will cause non-radiative recombination of carriers. At the same time, the mismatch of energy band arrangement will lead to carrier transfer barriers, thereby affecting the efficiency of carrier transmission and hindering the photoelectric conversion efficiency of the battery device. And because perovskite itself has a high humidity sensitivity, perovskite solar cells are extremely susceptible to external factors such as water and oxygen, thereby reducing the stability of the device.
[0005] A good way to solve the above problems is to add additives with specific structures to the perovskite precursor solution, and use the reaction between the additives and the perovskite material to passivate specific defects while adjusting the perovskite crystallization process, thereby improving the photoelectric conversion efficiency and device stability. Therefore, additives are crucial for achieving efficient and stable PSCs. However, the additives currently used are often single optimizations and cannot achieve comprehensive passivation of the entire device.
[0006] In order to reduce the adverse effects of moisture on the perovskite structure, improvement methods such as fine-tuning the perovskite composition and adding Lewis bases / acids are usually adopted, such as introducing alternative non-halide lead sources, formic acid pseudohalide anions to reduce anion / cation vacancies, and introducing hydrophobic additives. However, vacancies and defects on the surface of perovskite films will still chemically absorb surrounding moisture, inducing a hydration process and thus destroying the crystal structure. In addition, when the battery is continuously exposed to a harsh operating environment, the added passivators will diffuse and interact, so the attenuation of the passivation effect of existing additives is also inevitable.
[0007] Formamidinium lead iodide (FAPbI3) perovskite has high light absorption and long diffusion length, making it a host material for high-efficiency solar cells. The main intrinsic defect of FAPbI3 is that iodine vacancies induce strong electron localization and become deep traps and recombination centers when excited by light, which significantly shortens the carrier lifetime and does not fully utilize its superior performance. Therefore, how to better deal with intrinsic defects has become a key issue in realizing high-efficiency solar cells. Summary of the invention
[0008] In response to the problems raised in the above background technology, the purpose of the present invention is to provide a method and application for passivating defects in perovskite films, passivating surface defects of perovskite films from multiple dimensions, achieving comprehensive passivation of perovskite solar cells, and improving the photoelectric conversion efficiency and stability of perovskite solar cells.
[0009] In order to achieve the above technical effects, the technical solution of the present invention is implemented as follows:
[0010] In a first aspect, the present invention provides a method for passivating defects in a perovskite film, comprising the following steps:
[0011] Step 1, dissolving lead iodide in an organic solvent to prepare a lead iodide solution, wherein the organic solvent is a mixed solvent of DMF and DMSO, the DMF is N,N-dimethylformamide, and the DMSO is dimethyl sulfoxide;
[0012] Step 2, dissolving FAI and MACl in IPA to obtain an organic ammonium salt solution, and adding an additive to the organic ammonium salt solution to obtain an organic ammonium salt solution containing the additive; the FAI is iodoformamidine, the MACl is methylammonium chloride, and the IPA is isopropanol; the additive is a passivation molecule that can undergo an addition reaction with AX of the perovskite compound, and the passivation molecule contains a carboxyl group, an imino group, and an amino functional group;
[0013] Step 3, using a solution spin coating method, spin coating the lead iodide solution prepared in step 1 on the substrate and annealing to obtain a substrate containing a lead iodide film;
[0014] Step 4: using a solution spin coating method, spin-coat the organic ammonium salt solution containing additives prepared in step 2 onto the lead iodide film in step 3, and anneal to obtain a defect-passivated perovskite film.
[0015] Furthermore, the passivation molecule is an aminoalkyl acrylamide compound, including N-(3-aminopropyl) methacrylamide and its hydrochloride, N-(2-aminoethyl) methacrylamide and its hydrochloride, and N-(2-aminoethyl) acrylamide and its hydrochloride. Its chemical structure is as follows:
[0016] N-(3-aminopropyl)methacrylamide
[0017]
[0018] N-(3-Aminopropyl)methacrylamide hydrochloride
[0019]
[0020] N-(2-aminoethyl)methacrylamide
[0021]
[0022] N-(2-Aminoethyl)methacrylamide hydrochloride
[0023]
[0024] N-(2-aminoethyl)acrylamide
[0025]
[0026] N-(2-Aminoethyl)acrylamide hydrochloride
[0027]
[0028] The method for passivating defects of perovskite films provided by the present invention is to passivate the defects of perovskite films in multiple dimensions by introducing the above-mentioned passivating molecules that can react with AX of the perovskite compound into the perovskite, thereby achieving comprehensive passivation of perovskite solar cells and improving battery efficiency. The passivating molecules used in the present invention include amines and salts. After the salt passivating molecules are introduced into the perovskite, they are first deprotonated to form intermediate amines (amine passivating molecules), and then the intermediate amines react with FAI to generate new compounds. The new compounds passivate the defects of the perovskite film from multiple dimensions, including surface defects, body defects, interface defects, etc.
[0029] The passivation molecule AMCl (N-(3-aminopropyl) methacrylamide hydrochloride) is used as an example to illustrate the method of passivating defects in perovskite films of the present invention. The present invention introduces AMCl into perovskite, and AMCl first forms an intermediate amine by deprotonation, and then the intermediate amine reacts with FAI to form a new compound AMFA. The reaction mechanism is as follows:
[0030]
[0031] AMFA combines with lead iodide (PbI2) to form a new substance AMFAPb, which can induce the preferential growth of perovskite along a certain orientation, passivate the defects in the crystal and grain boundary, and compared with AMCl, AMFA has a stronger binding energy with PbI2; AMFA has a carboxyl group (C=O) and an imino group (—NH—), in which the carbonyl group can bind to the insufficiently coordinated Pb in the perovskite solution. 2+ Ion binding, or binding with other defective cations to form Lewis complexes, thereby passivating film defects, while the imino group increases the carboxyl group and Pb 2+ The coordination ability of AMFA can significantly reduce the defect state density in the perovskite film; at the same time, AMFA can delay the crystallization process of the perovskite film, inhibit phase change, and thus optimize the film performance. Therefore, the present invention passivates the surface defects of the perovskite film from multiple dimensions, which can effectively improve the photoelectric conversion efficiency of the perovskite solar cell.
[0032] At the same time, the present invention introduces passivation molecules into the perovskite, and the amino group (-NH2) of the passivation molecules will react with the FA of the perovskite. + The ions undergo chelation reaction to occupy the A position of the perovskite crystal skeleton, which increases the binding energy between perovskite and H2O molecules, thereby preventing the chemical reaction between perovskite and environmental water molecules, enhancing the moisture resistance of the perovskite film, and improving the stability of perovskite solar cells.
[0033] In some embodiments of the present invention, the lead iodide solution is doped with cesium iodide (CsI) and rubidium chloride (RbCl). Cesium iodide is an excellent scintillator material. By CsI doping, the light absorption performance of the film can be improved; by RbCl doping, PbI2 is converted into an inactive (PbI2)2RbCl compound, which effectively stabilizes the perovskite phase. Preferably, the concentration of lead iodide in the lead iodide solution is 1.5 mol / L, the mass concentration of cesium iodide is 2%, and the mass concentration of rubidium chloride is 3%.
[0034] The solvent is the medium for dissolving the perovskite precursor material, and its specific functional groups have an important influence on the coordination between the solvent and the perovskite precursor. The polarity of the solvent determines its coordination ability, thereby affecting the nucleation and growth of perovskite crystals and the morphology of the deposited perovskite film. Therefore, by adjusting the characteristics of the solvent, the film formation kinetics and film quality of the solution-processed perovskite film can be effectively controlled. In some embodiments of the present invention, the volume ratio of DMF to DMSO in the organic solvent is 9:1.
[0035] In some embodiments of the present invention, the mass concentration of FAI in the organic ammonium salt solution is 85 mg / mL, and the mass concentration of MACl is 15 mg / mL.
[0036] In some embodiments of the present invention, the additive in the organic ammonium salt solution containing additives is AMCl, and the mass concentration of AMCl is 0.5-1.5 mg / mL. More preferably, the mass concentration of AMCl is 1.0 mg / mL.
[0037] In a second aspect, the present invention provides the use of the above-mentioned method for passivating defects in perovskite films in the preparation of perovskite solar cells. The defect-passivated perovskite film obtained by the present invention is used as the perovskite layer of PSCs, and the maximum efficiency of PSCs is 25.40%, and the maximum open circuit voltage (Voc) is 1.18V. At the same time, the optimized PSCs have high environmental stability and still maintain 93% of the initial efficiency after being stored in ambient air for 1200h.
[0038] Furthermore, the material of the perovskite layer of the perovskite solar cell is lead formamidinium iodide perovskite.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] 1. The present invention introduces passivating molecules containing carboxyl, imino and amino functional groups into perovskite, and the passivating molecules react with AX of the perovskite compound to form new compounds. The new compounds passivate the defects of the perovskite film from multiple dimensions, including surface defects, body defects, interface defects, etc., thereby achieving comprehensive passivation of the perovskite solar cell and improving the photoelectric conversion efficiency of the perovskite solar cell; the defect-passivated perovskite film obtained by the present invention is used as the perovskite layer of PSCs, and the maximum efficiency of PSCs is 25.40%, and the maximum open circuit voltage (Voc) is 1.18V.
[0041] 2. The present invention introduces a passivation molecule containing an amino functional group into the perovskite. The amino group (-NH2) of the passivation molecule will react with the FA of the perovskite. +The ions undergo chelation reaction to occupy the A position of the perovskite crystal framework, which increases the binding energy between the perovskite and the H2O molecules, thereby preventing the chemical reaction between the perovskite and the environmental water molecules and enhancing the moisture resistance of the perovskite film. The PSCs optimized by the present invention have high environmental stability and thermal stability, and can still maintain 93% of the initial efficiency after being stored in ambient air for 1200 hours.
[0042] 3. The present invention introduces passivation molecules containing amino functional groups to prevent the chemical interaction between FA cations and environmental water molecules, which reasonably solves the problem that existing passivators cannot avoid the vacancies and defects on the surface of the perovskite film chemically absorbing the surrounding water, and also slows down the attenuation of the passivation effect.
[0043] 4. The multi-dimensional defect passivation method of the present invention can better deal with the intrinsic defects of FAPbI3. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is a schematic diagram of the structure of a nip-type perovskite solar cell prepared in Example 1 of the present invention;
[0045] Figure 2 This is a flow chart of the preparation of the perovskite film in Example 1 of the present invention;
[0046] Figure 3 Box plots of the photoelectric conversion efficiency (PCE) of the perovskite solar cell devices prepared in Examples 1 to 3 of the present invention and the comparative example;
[0047] Figure 4 Box plots of open circuit voltage (Voc) of perovskite solar cell devices prepared in Examples 1 to 3 of the present invention and the comparative example;
[0048] Figure 5 It is a box plot of the filling factor (FF) of the perovskite solar cell devices prepared in Examples 1 to 3 of the present invention and the comparative example;
[0049] Figure 6 Box plots of short-circuit current density (Jsc) of perovskite solar cell devices prepared in Examples 1 to 3 of the present invention and the comparative example;
[0050] Figure 7 The current density-voltage (JV) curves of the perovskite solar cell devices prepared in Example 2 of the present invention and the comparative example;
[0051] Figure 8 Spectral response characteristic curves of the perovskite solar cell devices prepared in Example 2 of the present invention and the comparative example;
[0052] Fig. 9The contact angle test diagram of the surface defect passivated perovskite film prepared in Example 2 of the present invention and the comparative example;
[0053] Fig.10 A graph showing the change in photoelectric conversion efficiency (PCE) of the perovskite solar cell devices prepared in Example 2 of the present invention and the comparative example as a function of storage time;
[0054] Fig.11 is the mass spectrum of the AMCl+FAI mixture in Example 4 of the present invention;
[0055] Fig.12 is the hydrogen nuclear magnetic resonance spectrum of AMCl in Example 4 of the present invention;
[0056] Fig.13 is the hydrogen nuclear magnetic resonance spectrum of FAI in Example 4 of the present invention;
[0057] Fig.14 The nuclear magnetic resonance hydrogen spectrum of the new complex obtained by mixing AMCl and FAI in Example 4 of the present invention;
[0058] Fig.15 is the carbon-1NMR spectrum of AMCl in Example 4 of the present invention;
[0059] Fig.16 is the carbon NMR spectrum of FAI in Example 4 of the present invention;
[0060] Fig.17 This is the carbon NMR spectrum of the new complex obtained by mixing AMCl and FAI in Example 4 of the present invention.
[0061] Legend:
[0062] 1-transparent electrode; 2-electron transport layer; 3-perovskite layer; 4-hole transport layer; 5-metal electrode. DETAILED DESCRIPTION
[0063] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with specific embodiments.
[0064] Lead iodide (PbI2, ≥98%) used in the following examples was purchased from Advanced Election Technology, Co. Ltd.
[0065] Stannous chloride dihydrate (SnCl2·2H2O, ≥99.99%, metals basis), urea (AR, 99%), hydrochloric acid, N-(3-aminopropyl)methacrylamide hydrochloride (AMCl, ≥98.0%, HPLC) were purchased from Aladdin. Thioglycolic acid (TGA, 98%) and rubidium chloride (RbCl2) were purchased from TCI.
[0066] NbCl5 (99.999%), cesium iodide (CsI, 99.999%, trace metals basis), lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) and 4-tert-butylpyridine (tBP) were purchased from Sigma-Aldrich.
[0067] Cobalt(III) tris(bis(trifluoromethylsulfonyl)imide) salt (Co(III)TFSI, FK209) was purchased from Greatcell Solar.
[0068] Formamidine hydroiodide (FAI), methylamine hydroiodide (MAI) and 2,2',7,7'-[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) were purchased from Xi'an p-oled.
[0069] Dimethylformamide (DMF), dimethyl sulfoxide (DMSO), chlorobenzene (CB), isopropyl alcohol (IPA) and acetonitrile were purchased from Sigma-Aldrich.
[0070] Example 1: Preparation of NIP-type perovskite solar cells
[0071] See also Figure 1 The structure of the perovskite solar cell prepared in this embodiment includes a transparent electrode 1, an electron transport layer 2, a perovskite layer 3, a hole transport layer 4, and a metal electrode 5. The transparent electrode 1 (anode) is fluorine-doped SnO2 conductive glass (FTO conductive glass), the electron transport layer 2 is chemically bath deposited SnO2, the perovskite layer 3 is FAPbI3 perovskite, the hole transport layer 4 is Spiro, and the metal electrode 5 (cathode) is Ag.
[0072] The preparation method is as follows:
[0073] (1) FTO glass cleaning
[0074] Use up water, isopropanol, acetone, and ethanol to ultrasonically process for 40 minutes each, and blow dry with an air gun diagonally downward along the side to check whether the FTO surface is clean, and discard the unclean FTO.
[0075] (2) Preparation of electron transport layer
[0076] A dense SnO2 layer was prepared on a cleaned FTO substrate (AGC22-8A, Advanced Election Technology, Co. Ltd.) by chemical bath deposition (CBD). The steps are briefly described as follows: (a) Dissolve 625 mg urea and 137.5 mg SnCl2·2H2O in 50 mL ultrapure water. (b) Add 625 μL hydrochloric acid (HCl), 12.5 μL thioglycolic acid (TGA) and 5 mol% NbCl5. (3) Pour the obtained CBD solution into a glass reaction vessel, and place the cleaned glass substrate vertically into the container. (c) React at 90°C for 5.5 h. After the reaction is completed, remove the FTO / SnO2 substrate from the reaction vessel. (d) Ultrasonic clean with ethanol and IPA for 5 min respectively and then blow dry. (e) Anneal the FTO / SnO2 substrate at 170°C for 60 min, cool to room temperature and set aside.
[0077] (3) Preparation of perovskite layer
[0078] PbI2 was dissolved in DMF and DMSO (volume ratio of 9:1) to prepare a 1.5 mol / mL PbI2 solution, and 2% CsI and 3% RbCl were doped at the same time. 85 mg FAI and 15 mg MACl were dissolved in 1 mL IPA to prepare an organic ammonium salt solution, and 0.5 mg / mL AMCl was dissolved in the aforementioned organic ammonium salt solution to obtain an organic ammonium salt solution with AMCl added.
[0079] Treat the SnO2 substrate with UV-visible light for 25 minutes, spin-coat the PbI2 solution at 1500 rpm for 30 seconds, and anneal the PbI2 film at 70°C for 1 minute. Then spin-coat the organic ammonium salt solution with AMCl at 1800 rpm for 30 seconds, and then move the perovskite film to ambient air and anneal it at 150°C (20-40 RH%) for 15 minutes. The formation of the perovskite layer is detailed in Figure 2 .
[0080] (4) Preparation of hole transport layer
[0081] The Spiro-OMeTAD solution was prepared by dissolving 91.4 mg of Spiro-OMeTAD in 1 ml of chlorobenzene, 35.6 μL of TBP, 21 μL of Li-TFSI ACN solution (520 mg / mL of acetonitrile solution) and 11 μL of FK209-Co(III)-TFSI ACN solution (300 mg / mL of acetonitrile solution). When the perovskite film cooled to room temperature, Spiro-OMeTAD was spin-coated on the perovskite film at 4000 rpm in a glove box for 30 s.
[0082] (5) Preparation of metal electrodes
[0083] Cathode silver was then evaporated on the hole transport layer, with a total thickness of 120 nm. After the metal electrode was deposited, all devices were placed in a desiccator overnight, and then the JV curves were measured.
[0084] Example 2: Preparation of NIP-type perovskite solar cells
[0085] The same as Example 1, except that the concentration of AMCl added to the organic ammonium salt solution in the preparation of the perovskite layer is 1.0 mg / ml.
[0086] Example 3: Preparation of NIP-type perovskite solar cells
[0087] The same as Example 1, except that the concentration of AMCl added to the organic ammonium salt solution in the preparation of the perovskite layer is 1.5 mg / ml.
[0088] Comparative example: Preparation of NIP-type perovskite solar cells
[0089] The same as Example 1, except that AMCl is not added to the organic ammonium salt solution during the preparation of the perovskite layer.
[0090] The photovoltaic performance and stability of the perovskite solar cells prepared in the above Examples 1 to 3 and the comparative example are analyzed below.
[0091] Figures 3 to 8 The photovoltaic characteristics of the perovskite solar cells assembled by using the surface defect passivated perovskite films prepared in Examples 1 to 3 of the present invention and the comparative example are shown, wherein: Figure 3 , Figure 4 , Figure 5 , Figure 6 The following are the photoelectric conversion efficiency (PCE), open circuit voltage (Voc), fill factor (FF) and short circuit current density (Jsc) of perovskite solar cells; Figure 7 The current density-voltage (JV) curves of the perovskite solar cell devices prepared in Example 2 of the present invention and the comparative example; Figure 8 Spectral response characteristic curves of the perovskite solar cell devices prepared in Example 2 of the present invention and the comparative example.
[0092] By comparing the parameters, it was found that: 1) Compared with the control example without adding AMCl, the light absorption layer film with the addition of AMCl improved the photovoltaic performance of PSCs to varying degrees; 2) In Example 2, the light absorption layer film with 1 mg / ml AMCl was added, and the perovskite solar cell showed the best photoelectric performance parameters, with an open circuit voltage of 1.17 V and a short circuit current density of 25.82 mA / cm 2 , the filling factor is 84.09% and the photoelectric conversion efficiency is 25.4%.
[0093] Fig. 9 and Fig.10 The environmental stability of the perovskite solar cells assembled with the surface defect passivated perovskite thin films prepared in Example 2 of the present invention and the comparative example is characterized, wherein Fig. 9 The contact angle test diagram of the surface defect passivated perovskite film prepared in Example 2 of the present invention and the comparative example is shown in FIG. Fig.10 The graph is a graph showing the photoelectric conversion efficiency (PCE) of the perovskite solar cell device prepared in Example 2 of the present invention and the comparative example as a function of storage time. Fig. 9 It can be seen that the water contact angle of the perovskite film without AMCl in the comparative example is 47°, and the water contact angle of the perovskite film with AMCl in Example 2 is 73°, indicating that the addition of AMCl significantly improves the hydrophobicity of the perovskite film, inhibits the penetration of water, and thus improves the stability of PSCs. Fig.10 The perovskite solar cell device prepared in Example 2 can maintain 93.1% of the initial efficiency after being stored in ambient air for 1200 hours.
[0094] Example 4: Characterization of the reaction mechanism of the mixture of AMCl and FAI
[0095] First, the AMCl+FAI mixture was tested by high-resolution mass spectrometry (HRMS). Fig.11 As shown in the figure, it was found that the mixture of AMCl+FAI gave a new complex with a molecular weight of 170.1287 and a corresponding molecular formula of C8H 16 N3O. Considering the possible deprotonation of AMCl and its interaction with FAI, the reaction pathway and products may be as follows:
[0096]
[0097] In order to prove the above conjecture, AMCl, FAI and the new complex obtained by mixing AMCl and FAI were respectively subjected to liquid 1 H NMR ( 1 H NMR) test and liquid 13 C NMR ( 13 C NMR) test, the test results are shown in Figures 12 to 17 .
[0098] Fig.12 This is the H NMR spectrum of AMCl. It can be seen that -NH-, -NH2, =CH2, -CH2-, and -CH3 groups in AMCl 1 H is located at 8.20ppm, 8.06ppm, 5.70ppm, 5.34ppm, 3.17ppm, 2.76ppm, 1.75ppm and 1.86ppm, respectively, with an integral ratio of 1:3:2:2:2:3:2.
[0099] Fig.13 This is the H NMR spectrum of FAI. It can be seen that =NH, -NH and =CH- groups in FAI 1 H is located at 8.97ppm, 8.69ppm and 7.86ppm, with an integral ratio of 2:2:1.
[0100] Fig.14 This is the H NMR spectrum of the new complex obtained by mixing AMCl and FAI. It can be seen that the -NH, =CH, =NH, =CH2, -CH2 and -CH3 groups in the new complex 1 H is located at 9.09ppm, 8.81ppm, 8.14ppm, 7.91ppm, 5.69ppm, 5.35ppm, 3.19ppm, 2.77ppm, 1.73ppm and 1.86ppm, respectively, with an integral ratio of 1:1:1:2:2:2:2:2:3:2.
[0101] Fig.15 This is the carbon NMR spectrum of AMCl. It can be seen that the carbonyl, double bond, -CH2 and -CH3 groups in AMCl 13 C is located at 168.16ppm, 140.20ppm, 119.74ppm, 37.04ppm, 36.24ppm, 27.62ppm and 19.12ppm respectively.
[0102] Fig.16 This is the carbon NMR spectrum of FAI. 13 C is located at 157.63 ppm.
[0103] Fig.17 This is the C NMR spectrum of the new complex obtained by mixing AMCl and FAI. It can be seen that the carbonyl, double bond carbon, carbon-carbon double bond, -CH2 and -CH3 groups in the new complex 13 C is located at 168.24ppm, 157.72ppm, 140.19ppm, 119.76ppm, 36.16ppm, 36.27ppm, 27.71ppm and 19.11ppm respectively.
[0104] In summary, it can be seen that the new complex 1 H NMR and 13 C NMR is consistent with AMFA, and the hypothesis is confirmed.
[0105] The above are only preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be regarded as limiting the present invention, and the protection scope of the present invention should be based on the scope defined by the claims. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A method for passivating defects in perovskite films, Features: The following steps are involved: Step 1, dissolving lead iodide in an organic solvent to prepare a lead iodide solution, wherein the organic solvent is a mixed solvent of DMF and DMSO, the DMF is N,N-dimethylformamide, and the DMSO is dimethyl sulfoxide; Step 2, dissolving FAI and MACl in IPA to obtain an organic ammonium salt solution, and adding an additive to the organic ammonium salt solution to obtain an organic ammonium salt solution containing the additive; the FAI is iodoformamidine, the MACl is methylammonium chloride, and the IPA is isopropanol; the additive is a passivation molecule that can undergo an addition reaction with AX of the perovskite compound, and the passivation molecule contains a carboxyl group, an imino group, and an amino functional group; Step 3, using a solution spin coating method, spin coating the lead iodide solution prepared in step 1 on the substrate and annealing to obtain a substrate containing a lead iodide film; Step 4: using a solution spin coating method, spin-coat the organic ammonium salt solution containing additives prepared in step 2 onto the lead iodide film in step 3, and anneal to obtain a defect-passivated perovskite film.
2. The method according to claim 1, Features: The passivation molecules include N-(3-aminopropyl)methacrylamide and its hydrochloride, N-(2-aminoethyl)methacrylamide and its hydrochloride, and N-(2-aminoethyl)acrylamide and its hydrochloride.
3. The method according to claim 1, Features: The lead iodide solution is doped with cesium iodide and rubidium chloride.
4. The method according to claim 3, Features: The lead iodide concentration in the lead iodide solution is 1.5 mol / L, the mass concentration of cesium iodide is 2%, and the mass concentration of rubidium chloride is 3%.
5. The method according to claim 1, Features: The volume ratio of DMF to DMSO in the organic solvent is 9:
1.
6. The method according to claim 1, Features: The mass concentration of FAI in the organic ammonium salt solution is 85 mg / mL, and the mass concentration of MACl is 15 mg / mL.
7. The method according to claim 1, Features: The additive in the organic ammonium salt solution containing additives is AMCl, the mass concentration of the AMCl is 0.5-1.5 mg / mL, and the AMCl is N-(3-aminopropyl) methacrylamide hydrochloride.
8. The method according to claim 7, Features: The mass concentration of AMCl in the organic ammonium salt solution containing additives is 1.0 mg / mL.
9. Use of the method according to any one of claims 1 to 8 in preparing perovskite solar cells.
10. The use according to claim 9, Features: The material of the perovskite layer of the perovskite solar cell is lead formamidinium iodide perovskite.
Citation Information
Patent Citations
Method for preparing perovskite thin film based on additive engineering and photoelectric application thereof
CN112582544A
Preparation method of efficient and stable titanium ore solar cell
CN114914362A
Application of 2-[carbamoyl(methyl)amino]acetate hydrochloride in perovskite solar cells
CN114937747A
Perovskite solar cell and preparation method thereof
CN116761446A
